(untitled) (Al-Mukhtar Journal of Basic Sciences, 2025)
This study investigates the fundamental properties and applications of soft simply open sets within soft topological spaces. We establish novel theoretical frameworks by: 1- Characterizing their relations to soft separation axioms (particularly near normality). 2- Demonstrating their duality through soft simply interior (closure) operations, and proving their efficacy in handling uncertain data structures. The results highlight how soft simply open sets bridge theoretical topology with computational applications, offering new tools for complex data analysis. Future directions include extensions to soft compactness and connection with fuzzy neural networks.